Decreasing of threats to the condition of environment of Turkmenistan at the hydrocarbon and mineral raw materials mining - Ginkul, A. P.; Krivileva, S. P. (NTU "KhPI", 2017)
The main ecological problems of Turkmenistan caused by the use of environmentally hazardous methods of exploration and production of hydrocarbon and mineral raw materials are analyzed. The main methods used in Turkmenistan for the extraction and transportation of oil and gas and the environmental consequences of their use are listed. The main causes of the deterioration of the natural environment of Turkmenistan during the extraction of hydrocarbons on the shelf of the Caspian Sea have been identified. Technological innovation in the exploration and production sector has equipped the industry with the equipment and practices necessary to continually increase the production of natural gas to meet rising demand. Hense formulated the prior areas for further rising of environmental safety in the oil and gas sector and extraction of mineral raw materials: wide introduction into the production of new innovative energy-efficient technologies and the latest achievements of the world science in the entire production cycle - from geologic explorations, development and development of production to transportation, storage and use of natural resources.

Проаналізовані основні екологічні проблеми Туркменістану, викликані використанням екологічно небезпечних методів розвідки і видобуванні вуглеводневої і мінеральної сировини. Розглянуті основні методи видобування і транспортування нафти, газу і мінеральної сировини, що використовуються у Туркменістані, і екологічні наслідки їх застосування. Виявлені головні причини погіршення природного середовища Туркменістану при видобуванні вуглеводнів на шельфі Каспійського моря. Сформульовані пріоритетні напрями подальшого підвищення екологічної безпеки у нафтогазовому ceкторі і при видобуванні мінеральної сировини: широкомacштaбнe впровадження у виробництво новітніх енeргоефeктивных тeхнологій і останніх здобутків світової нaуки за усім циклом виробництва – від гeологорозвідних робіт і розробки родовищ до трaнcпортування і використання природних ресурсів.
Зниження загроз стану довкiлля Туркменістану при видобуванні вуглеводневої та мінеральної сировини
Keywords: hydrocarbon raw materials; equipment; Turkmen gas; exploration methods; drilling; dangerous extraction; open manner extraction; greening; soil degradation; landscape disturbance; desertification; binding; сировина вуглеводнева; родовища; методи розвідки; буріння; екологізація; деградація ґрунту; порушення ландшафту; опустелювання; біорізноманіття